Damage of the foliage of horse chestnut by larvae of chestnut leaf-mining moth in Grodno green areas during summer - Roginsky, Alexey S.; Hliakouskaya, Katsiaryna I. (Journal of the Belarusian State University. Ecology, 2019)
We determined the relative damage area on the leaves of horse chestnut (Aesculus hippocastanum L.; Sapindaceae) by larvae of chestnut leaf-mining moth (Cameraria ohridella Deschka & Dimič, 1986) in Grodno green areas. The values of this indicator varied from 3,54 to 85,08 % in June-July 2017–2018 which corresponds to the loss of plant’s ornamentally from insignificant to catastrophic. The damage level of the leaves by miners was higher in parks (Rumlevo, Kolozhsky) where sweeping of leaf litter with cradles of larvae in mines was carried out partially. At the same time, the level of leaf damage was lower in street stands where leaf litter was cleaned carefully.
Keywords: Cameraria ohridella; biological invasions; plant introduction; decorative plantings; black book